Contracting Out National Immunization Program Does Not Improve Vaccination Rate Nor Socioeconomic Inequality: A Case Study of Seasonal Influenza Vaccination in South Korea - Moon, Daseul; Kim, Saerom; Kim, Myoung-Hee; Jeong, Dawoon; Choi, Hongjo (Frontiers in Public Health, 2021)
The objective of the present study was to investigate if the policy for contracting out the Korean influenza National Immunization Program (NIP) for individuals aged ≥ 65 years affects a reduction in vaccination inequality based on gender and socioeconomic position (SEP). In South Korea, initially only public health centers provided influenza vaccination for free; however, starting from the fall of 2015, the program was expanded to include private medical institutions. The policy was expected to improve overall vaccination rate and reduce its inequality, through improving access to vaccination. The present study analyzed how the gap in the vaccination rate changed between before and after contracting out. A multivariate logistic regression model stratified by gender and SEP of individuals aged ≥ 65 years was used. The study also analyzed changes in the unvaccinated rates between before and after contracting out based on an interrupted time series model. The gap in the unvaccinated rate based on SEP present prior to contracting out of the NIP for individuals aged ≥ 65 years did not decrease afterwards. In particular, the step changes were 0.69% (95% confidence interval [CI]: -2.28, 0.24) and -0.15% (95% CI: -2.76, 2.45) in men and women, respectively. In the pre-policy period, among women, the unvaccinated rate of the medical aid beneficiaries group was 1.22-fold higher (95% CI: 1.12, 1.32) than that of the health insurance beneficiaries, and the difference was not reduced post-policy implementation (odds ratio: 1.27, 95% CI: 1.20, 1.36). The findings of the study were that contracting out of the NIP was not effective in improving vaccination rate nor resolving vaccination inequality. Future studies should focus on identifying the mechanism of vaccination inequality and exploring measures for resolving such inequality.